Recurring oral erythema multiforme-like lesions elicited by COVID-19 infection: a case report - Al-Ak’hali, Mohammed Sultan; Esam Halboub,; Wael Ibraheem,; Hamza Khalid Khan,; Hummadi, Abdulkreem Mohammed (Brazilian Dental Science, 2022)
Oral mucosa could be the first site infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) –thecausative agent of coronavirus disease 2019 (COVID-19). Indeed, different oral and paraoral lesions, conditionsand symptoms have been reported in patients with COVID-19. Experts thought that such oral lesions could besecondary to the COVID-19-associated deterioration of systemic health or due to treatments of COVID-19. Wepresent here a case of a 24-year-old male presented with painful multiple ulcers involving the labial and buccalmucosae bilaterally after a while of feeling very mild symptoms that laboratory-confirmed by reverse-transcriptionpolymerase chain reaction to be COVID-19. Involvement of eyes was also reported. The above clinical presentationwas consistent with minor erythema multiform. Many topical preparations were prescribed but with limitedimprovement. Hence, oral prednisolone was prescribed with a 40-mg loading dose that was tapered by 10 mgevery 3 days. Complete healing of oral mucosa was observed on the 10 day. Strikingly, the patient got affectedwith the second episode of similar oral lesions 5 months later without any apparent triggering factors, suggestivea long term effects of COVID-19 in a subset of patients. The present case report provides dentists with usefulinformation and increases their awareness regarding possible involvement of oral cavity with multiple ulcerativelesions associated with COVID-19.KEYWORDSOral erythema multiforme; Oral manifestations; COVID-19; Case report.